2010
DOI: 10.1016/j.vetmic.2009.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Torque teno virus: Determination of viral genomic loads by genogroup-specific multiplex rt-PCR, detection of frequent multiple infections with genogroups 1 or 2, and establishment of viral full-length sequences

Abstract: Torque teno virus: Determination of viral genomic loads by genogroup-specific multiplex rt-PCR, detection of frequent multiple infections with genogroups 1 or 2, and establishment of viral full-length sequences. Veterinary Microbiology, Elsevier, 2009, 143 (2-4) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 34 publications
2
47
0
2
Order By: Relevance
“…The first antibody survey revealed a relatively high rate of seropositivity to TTSuV2 in conventional pigs from different sources but not in gnotobiotic pigs. This result correlates with the ubiquitous nature of TT viruses and their high prevalence as detected by PCR and quantitative PCR techniques (Gallei et al, 2010;Huang et al, 2010;Kekarainen et al, 2006;Jarosova et al, 2011). The main structural protein of the virus is the nucleocapsid protein (thought to be coded by ORF1), the largest structural protein of the virus particle.…”
mentioning
confidence: 75%
“…The first antibody survey revealed a relatively high rate of seropositivity to TTSuV2 in conventional pigs from different sources but not in gnotobiotic pigs. This result correlates with the ubiquitous nature of TT viruses and their high prevalence as detected by PCR and quantitative PCR techniques (Gallei et al, 2010;Huang et al, 2010;Kekarainen et al, 2006;Jarosova et al, 2011). The main structural protein of the virus is the nucleocapsid protein (thought to be coded by ORF1), the largest structural protein of the virus particle.…”
mentioning
confidence: 75%
“…Ataxia and hind limb paresis were observed in 2 dual-infected (PCV-2b/BVDV-1-like virus) germ-free pigs. Signs were transient in 1 animal (days [10][11][12][13][14][15][16]. The other pig also had partial tongue paralysis; signs in this animal were present at days 10-22 (end of study).…”
Section: Clinical Signsmentioning
confidence: 87%
“…Real-time PCR for TTV-1 was performed using sequence-specific primers and a probe bearing a 5′ FAM and 3′ MGB (minor groove binder) quencher. 12 Nested PCR for TTV-2 were performed as previously described. 20 …”
Section: Polymerase Chain Reactionmentioning
confidence: 99%
“…It has been demonstrated that a single pig can be infected with more than one strain of the TTSuV genera (Huang et al 2010, Gallei et al 2010, Leme et al 2013). This is probably because molecular variation in the TTSuV genomic sequences could lead to antigenic differences as a mechanism to avoid the host immune response.…”
Section: Discussionmentioning
confidence: 99%
“…TTSuV is widely distributed in pig herds in a number of countries in Asia, Europe, and America (McKeown et al 2004, Niel et al 2005, Gallei et al 2010, Savic et al 2010, Pérez et al 2011, Leme et al 2012. TTSuV infection is found in both healthy and diseased pigs, and a number of studies have been performed to determine the importance of the virus and the role it plays in infectious diseases (Meng 2012).…”
Section: Introductionmentioning
confidence: 99%